Effects of Social Media Marketing on Buying Interest - Sopia, Sopia Safitriyani; Muslichah, Istyakara (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to analyze Instagram's social media marketing activities have a positive and significant effect on brand equity, buying interest, word-of-mouth marketing. The author updates the research model that has previously been carried out. The industry that the researchers chose was the dairy industry. This study uses SOR (Stimulus Organism Response) theory as the basis for research. This researcher used quantitative methods with 192 respondents using the Roscoe formula with purposive sampling techniques. Data in this study was obtained by filling out questionnaires by respondents. There are 28 questions that must be answered by respondents through Google Form. Researchers analyzed the results of the validity of the Fornel Lacker Criterion discriminant. This study is intended to determine the impact generated from social media marketing activities (SMMA) and buying interest in children's milk products. This research shows that Instagram's social media marketing activities have a positive and significant effect on buying interest. Brand equity has a positive and significant effect on word-of-mouth marketing. The result obtained for marketing effectiveness is to use word of mouth marketing which has a positive and significant effect on respondents' buying interest.